Deep transfer learning on continual learning - Sousa Leite de Carvalho, Marcus Vinicius (Nanyang Technological University, 2023)
Artificial intelligent agents acting in the real world interact with a multitude of data streams. As a result, they must attain, accumulate and record various tasks from non-stationary data distributions. In addition, self-governing computational agents must acquire an understanding of new experiences and transfer knowledge from prior learning over a long period. Continual learning or lifelong learning refers to the capacity to continuously acquire new knowledge, adapt to changing circumstances, and integrate new experiences with previously learned ones over an extended span of time.